2017
DOI: 10.1111/jgh.13807
|View full text |Cite
|
Sign up to set email alerts
|

DA‐9701 improves colonic transit time and symptoms in patients with functional constipation: A prospective study

Abstract: DA-9701 accelerates colonic transit and safely improves symptoms in patients with functional constipation. Therefore, we suggest that this novel agent could help to treat patients with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(153 reference statements)
1
9
0
Order By: Relevance
“…Fourth, the outcome measures were patients’ and clinicians’ scales; thus, there was a lack of objective measure of GI motility in this trial. However, previous studies demonstrated a significant gastrokinetic effect of DA‐9701 with dynamic magnetic resonance imaging, 22,24 thereby supporting the results of the present study. One previous study reported that DA‐9701 enhances colonic transit time in patients with functional constipation 23 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Fourth, the outcome measures were patients’ and clinicians’ scales; thus, there was a lack of objective measure of GI motility in this trial. However, previous studies demonstrated a significant gastrokinetic effect of DA‐9701 with dynamic magnetic resonance imaging, 22,24 thereby supporting the results of the present study. One previous study reported that DA‐9701 enhances colonic transit time in patients with functional constipation 23 .…”
Section: Discussionsupporting
confidence: 91%
“…However, in animal studies with 50 to 100 times higher doses of DA‐9701 than a therapeutic oral dose (which is a similarly high dose for humans), the maximum concentrations of the 2 constituents in the brain were much lower than the half‐maximal inhibitory concentration values for D 2 ‐receptor antagonism by both of them 56 . This means that DA‐9701 with a therapeutic dose hardly has central antidopaminergic activity and it does not significantly induce hyperprolactinemia in humans as consistently reported by several independent studies 5,21,24 . This trial was focused on GI symptoms and GI health‐related QoL in patients with PD, and most participants had stable parkinsonian motor features without fluctuation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…for 24 days was associated with a significantly reduced colonic transit time (CTT) ( p = 0.001) and decreased segmental CTT ( p < 0.001). In addition, all constipation-related subjective symptoms, including spontaneous bowel movement frequency, significantly improved compared to those before treatment, without any serious adverse effects [99].…”
Section: Clinical Studies Of Da-9701mentioning
confidence: 99%
“…DA-9701 has an affinity for the 5-HT 4 receptor, and some animal studies have showed it increases colonic motility (122,129). A prospective and single-center study investigated the efficacy of DA-9701 in 27 patients with functional constipation by Rome III criteria (135). After administration of 30 mg DA-9701 three times a day for 24 days, spontaneous bowel movement, stool form, and constipation-related subjective symptoms were improved.…”
Section: Constipationmentioning
confidence: 99%